Evaluasi Penerapan Sanitasi Dalam Meningkatkan Kualitas Pelayanan Air Bersih Di Lembaga Pemasyarakatan Pemuda Kelas III Langkat - Edy Mulianta Milala; Imam Santoso (CV. Ulil Albab Corp, 2025)
This study evaluates sanitation in improving the quality of clean water services at the Class III Langkat Youth Penitentiary in accordance with the Water Management Standards issued by the Directorate of Corrections. The need for quality clean water in the correctional environment is very important, because poor water quality can cause various health problems, such as diarrhea and skin diseases. This study is a type of qualitative descriptive research using interview research methods, observation and library studies or documentation. The data sources taken in this study are primary data and secondary data. The data analysis techniques used in this study are data reduction, data presentation and drawing conclusions. The results of the study indicate that although water quality meets several standards, periodic sanitation evaluations and updates are needed to ensure better water management and prevent disease. The challenges identified include inadequate infrastructure and limited resources. Recommendations are given to improve the sanitation system and provide safer and more reliable access to clean water for inmates, in accordance with health and human rights standards.